Physicobiochemical Characteristics and Chondrogenic Differentiation of Bone Marrow Mesenchymal Stem Cells (hBM-MSCs) in Biodegradable Porous Sponge Bovine Cartilage Scaffold - Dwikora Novembri Utomo; Ferdiansyah Mahyudin; Teddy Heri Wardhana; Purwati Purwati; Febrian Brahmana; Agrippina Waya Rahmaning Gusti (International Journal of Biomaterials)
Tissue engineering had been believed to overcome the limitation of cartilage lesions treatment. Nowadays the studies focus on using mesenchymal stem cells in scaffold. A biodegradable porous sponge bovine cartilage scaffold is expected to have the physicobiochemical characterization to promote chondrogenic differentiation of hBM-MSCs. Scaffold from bovine cartilage was printed in 5 mm diameter sponge, categorized into nondecellularized (SBCS) and decellularized (DSBCS). Physical characteristics (pore diameter and interconnectivity) were done using a Scanning Electron Microscope (SEM). Biodegradability assessment used Phosphate Buffered Saline in 15, 30, 60 minutes, 6, 24, 48, 72 hours, and 1, 2 weeks. The swelling ratios were counted in 5, 10, 15, 30, 60, and 360 minutes. Biochemical characteristics were obtained by enzyme-linked immunosorbent assay for type II collagen, aggrecan, and Transforming Growth Factors-β (TGF-β). Data were statistically compared. hBM-MSCs were seeded on both scaffolds. Histological examination used hematoxylin-eosin taken at the 2nd and 4th weeks after seeding. There was no significant difference (p=0.473; p=0.142) on mean porosity 90.07 ± 4.64% vs. 88.93 ± 4.18% and pore diameter 111.83 ± 14.23 μm vs. 105.29 ± 11.14 μm assessment between SBCS and DSBCS groups. Scaffolds from both groups showed pore interconnectivity. DSBCS group had faster biodegradability. SBCS group sweals better. SBCS group contains type II collagen, aggrecan, and TGF-β with mean values 380.78 ± 18.63 ng/ml, 30.71 ± 4.50 ng/ml, and 130.12 ± 7.73 ng/ml, respectively, while DSBCS contained type II collagen, aggrecan, and TGF-β with mean values 64.83 ± 13.54 ng/ml, 8.41 ± 2.38 ng/ml, and 16.39 ± 4.49 ng/ml, respectively. The results were statistically different (p<0.001). Chondrocytes were found within scaffold on the 2nd and 4th weeks. Physicobiochemical characteristic of biodegradable sponge bovine cartilage scaffold promotes chondrogenic differentiation of hBM-MSCs.